(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
As a result of the development of information and communication technologies (ICT) and Internet electronic interaction at all levels in the organizations and the use of various electronic services has become part of our everyday life. The past few decades have been characterized by a tremendous growth in the amount of data generated. At the same time, digital data are subject to malicious and accidental threats, due to the presence of vulnerabilities in the protection of information systems. Unauthorized access, malware, zero-day attack, data leakage, denial of service (DoS), and phishing have increased exponentially in recent years. Data leakage occurs when sensitive data and confidential information is revealed to unauthorized parties. Data leakage is one of the main targets of any insider threat. Over the last few years, the challenge of dealing with insider threats has been recognized and various methods have been proposed to address such problems. Therefore, most proposed internal threat detection methods work towards data leakage prevention (DLP). This paper addresses the data leakage prevention and detection (DLPD) as some of the most critical cybersecurity issues nowadays. The used DLP techniques and technologies have been explored briefly. As the study aims to reveal the scientific interests in the DLP domain we tried to provide a comprehensive overview of academic publications. Finally, the paper focuses on what drives the DLP domain, the challenges and opportunities the digital configurations are faced in the context of data flow monitoring, prevention and detection.